Advancements in intratumoral therapies for liver tumors - Raman, Steven S.; Cutler, Neal R.; Sramek, John J.; Hecht, J. Randolph; Finn, Richard S.; Anand, Sidharth R.; Chiang, Jason; Lu, David S. (Frontiers in Oncology, 2026)
Liver tumors, including hepatocellular carcinoma (HCC), intrahepatic cholangiocarcinoma (iCCA), and liver-dominant metastases, remain associated with high mortality despite advances in systemic therapy. Intratumoral therapies have emerged as a promising strategy to achieve high local drug concentrations, modulate the tumor microenvironment, and enhance systemic anti-tumor immunity while limiting systemic toxicity. Although intratumoral approaches have demonstrated clinical success in melanoma, their translation to liver malignancies presents unique biological, immunologic, and technical challenges. This review synthesizes clinical evidence from the past decade evaluating intratumoral therapies for primary and metastatic liver tumors, including oncolytic viruses, cell-based immunotherapies, in situ immunomodulators, intratumoral chemotherapy, and combination strategies with locoregional or systemic treatments. Across early- and late-phase trials, intratumoral therapies have produced heterogeneous outcomes, ranging from tumor necrosis and disease stabilization to occasional systemic (abscopal) responses, while several large studies have failed to demonstrate survival benefit. These mixed results reflect the liver’s highly tolerogenic immune microenvironment, characterized by abundant myeloid-derived suppressor cells, regulatory T cells, and abnormal vasculature that limit immune activation and drug distribution. We highlight key determinants of efficacy, including tumor biology, delivery technique, dosing strategy, and rational therapeutic combinations. Technical considerations such as image-guided injection, intratumoral pressure, and standardization of administration are reviewed, alongside emerging biomarkers, including immune, molecular, and imaging-based markers, that may enable improved patient selection. Overall, current evidence suggests that intratumoral therapies alone are rarely sufficient for liver tumors but may provide meaningful benefit when integrated into multimodal regimens. Future progress will depend on optimized combination strategies, standardized delivery approaches, and validated biomarkers to support personalized application in liver cancer.